2012
DOI: 10.1177/1545109712461553
|View full text |Cite
|
Sign up to set email alerts
|

Low Tuberculosis Knowledge among HIV-Infected Patients in a High HIV Prevalence Region within Southeast India

Abstract: HIV-infected patients in southeast India have poor knowledge of TB and the methods by which it is spread. Scale-up of patient-directed educational programs is necessary to help control TB in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…This study and other studies have consistently shown that knowledge of HIV patients regarding tuberculosis was poor and recommended a specific and targeted education among this at-risk group [ 5 , 18 , and 19 ]. In this research, significantly higher mean knowledge scores seen in the intervention group compared to the control group revealed that there was an improvement in knowledge among respondents that received the intervention.…”
Section: Discussionsupporting
confidence: 57%
“…This study and other studies have consistently shown that knowledge of HIV patients regarding tuberculosis was poor and recommended a specific and targeted education among this at-risk group [ 5 , 18 , and 19 ]. In this research, significantly higher mean knowledge scores seen in the intervention group compared to the control group revealed that there was an improvement in knowledge among respondents that received the intervention.…”
Section: Discussionsupporting
confidence: 57%
“…Aspects related to the availability and length of treatment, as well as the importance of completing the entire treatment are being effectively communicated to the large majority of TB patients. Our estimates of Indian TB patient knowledge are higher than some others in the literature [ 7 – 12 ]; perhaps because this cohort represented urban TB patients whereas most available knowledge, attitude, and belief assessments regarding TB were conducted on non-TB populations in rural areas. Though rates of TB knowledge were higher than in other studies even at the beginning of DOTS, TB patients may have acquired additional TB knowledge as they progressed through the patient pathway before being enrolled in DOTS.…”
Section: Discussionmentioning
confidence: 67%
“…This is higher than in other studies of Indian people without TB where only 20%–56% could correctly identify the mode of transmission. [ 7 – 9 ] About two thirds knew that TB is communicable (67.2%, CI: 65.6%, 68.7%), a slightly lower share likely due to some confusion over the definition of a communicable disease. Knowledge about TB symptoms was more limited though.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, stigma was found to be associated with TB and HIV and has been cited in many studies as a predictor of negative health-seeking behaviour. 5 , 6 , 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%